Presumed Onchocerciasis Chorioretinitis Spilling over into North America, Europe and Middle East - Ahmad Mansour; Linnet Rodriguez; Hana Mansour; Madeleine Yehia; Maurizio Battaglia Parodi (Diagnostics, 2023)
Background: Newer generation ophthalmologists practicing in the developed world are not very familiar with some tropical ocular diseases due to the absence of reports in the ophthalmic literature over the past thirty years. Because of world globalization or due to influx of immigrants from sub-Saharan Africa, exotic retinal diseases are being encountered more often in ophthalmology clinics. Methods: A multicenter case series of chorioretinitis or optic neuritis with obscure etiology that used serial multimodal imaging. Results: Four cases qualified with the diagnosis of presumed ocular onchocerciasis based on their residence near fast rivers in endemic areas, multimodal imaging, long term follow-up showing progressive disease and negative workup for other diseases. Characteristic findings include peripapillary choroiditis with optic neuritis or atrophy, subretinal tracts of the microfilaria, progressive RPE atrophy around heavily pigmented multifocal chorioretinal lesions of varying shapes, subretinal white or crystalline dots, and response to ivermectin. Typical skin findings are often absent in such patients with chorioretinitis rendering the diagnosis more challenging. Conclusions: Familiarity with the myriad ocular findings of onchocerciasis, and a high-degree of suspicion in subjects residing in endemic areas can help in the correct diagnosis and implementation of appropriate therapy. Onchocercal chorioretinitis is a slow, insidious, progressive, and prolonged polymorphous disease.